TRADITIONAL, COMPLEMENTARY AND ALTERNATIVE MEDICINE USE OF CHRONIC DISEASE PATIENTS IN A COMMUNITY POPULATION IN MYANMAR - Peltzer, Karl; Oo, Win Myint; Pengpid, Supa (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of this study was to assess the prevalence and associated factors of Traditional, Complementary andAlternative Medicine’s (TCAM) use of chronic disease patients in a community setting in Myanmar.Materials and Methods: A cross-sectional community survey was conducted in the Kyauk Tan Township with the InternationalComplementary and Alternative Medicine Questionnaire (I-CAM-Q).Results: Of the 1600 participants in the survey, the overall prevalence of any TCAM use (providers, products or self-care) was95.1% (TCAM provider= 14.6%, TCAM products=65.0%, and self-help TCAM=86.2%) in the past 12 months. For all differenttypes of TCAM providers, TCAM products and self-help TCAM more than 90% of participants perceived the TCAM as very orsomewhat helpful. In multivariate logistic regression analysis, older age, no formal education, rural residence and having two ormore chronic conditions were associated with any TCAM use.Conclusions: TCAM use, especially TCAM products and self-help TCAM, seem to be common in Myanmar.